'Another accreditation? what's the point?' effective planning and implementation for specialised accreditation. Issue 2 (4th May 2019) - Staub, Donald
ABSTRACT: Globally, attention to quality and accreditation in higher education continues trending upward. This is attributable to a number of factors, such as the internationalisation of higher education, stakeholders demanding accountability, international rankings; parents and students wanting assurance that a diploma equals employment. Universities and individual programmes pursue accreditation because it is mandated; others to stand out in a crowded marketplace. The somewhat voluntary pursuit of accreditation raises two relevant questions. First, to what degree do teachers and administrators perceive its value? Second, for institutions and programmes seeking accreditation for the first time, is there a strategic approach that may effectively help prepare for the accreditation process? First, these issues are explored with teachers and administrators who have experienced the accreditation process. Second, using Bolman and Deal's four frames for organisational analysis, this research proposes a strategic approach to analysing the institutional context and laying the foundation for successful accreditation efforts.